P135 Prevalence Of Sensitisation To Soya Flour In The Baking Industry Within The Uk. (10th November 2014) - Cannon, J; Jones, M; Welch, J; Fitzgerald, B; Szram, J; Cullinan, P
Abstract : Introduction: Soya flour is routinely used as a baking additive to increase shelf life, improve colour and introduce a nutty flavour to bread. Although a large number of bakers are exposed to soya flour, there is little information as to the prevalence of sensitisation to soya flour in the baking industry. One study reports sensitisation to soya flour in four bakers who were sensitised to flour and alpha amylase and a bronchial challenge to soya flour elicited an immediate or dual asthmatic response. Studies in soy processing plant (slightly different to bakeries) report soy-specific IgE in 21% of soy processing workers compared with only 4% in health care workers, suggesting soya is an important occupational allergen in the soy processing industry. Methods: To determine prevalence of sensitisation to soya flour in bakery workers, we carried out skin prick testing to soya flour (Allergopharma 598) in bakery workers exposed to soya flour (n = 196) and in non-bakery controls (n = 50), who attended an occupational lung disease clinic. Skin tests were categorised as positive if they induced a wheal with a mean diameter of ≥2 mm greater than the response to a negative (saline) control and histamine was used as a positive control. Results: In a total of one hundred and ninety five bakery workers exposed to soya, forty two bakers were sensitised to soya flour (21%), and forty of those bakers were also sensitised to either flour and or alpha amylase (95%) In comparison, none of the control group (n = 50) were sensitised to soya flour. Conclusion: In our preliminary study of bakery workers exposed to soya flour, we found that around a fifth of the population were sensitised to soya flour. The clinical significance of soya flour need further investigation, although it seems prudent to include soya flour in the diagnostic tests for bakers asthma.